A Preliminary Study on Impacts of Accounting Software Utilization on Skills of Postgraduate International Accounting Students - Muftah, Mohamed Abreima A. (2011)
As technology evolution continue to reduce the costs associated with hardware and software for classroom instructions, the instructional environment and teaching pedagogy of business faculty in accounting particularly also have evolved over time. While technology integration in accounting education has been a constant focal point of discussion in recent years, the extant and the usage pattern of various classroom technologies in accounting instructions is unclear. The purpose of this thesis was to encourage the use of computers for accounting purposes (accounting software utilization) and to know the attitudes towards the computer by accounting international postgraduate students in UUM. Questionnaires were distributed to 106 UUM accounting international postgraduate students in UUM in order to acquire their conception on the impact of studying a course in using computers for accounting purposes and on attitudes towards the computer skills perceived by accounting international postgraduate students. Five variables were involved in the regression analysis among which three independent variables (age, GPA and prior experience in using computers) related to demographic characteristics of respondents, an independent variables on attitude (attitudes toward using computer for accounting) and a dependent variable (perceived skills in using computers for accounting purposes). One of the major results emphasized that more or less 26.3% of the variance of students' perceptions was accounted for by its linear relationship with the variables known as GPA, prior experience and their attitudes toward using the computers.